Shared genetic features inference among hypoxia-ischemia diseases in the presence of heterogenous omics data based on a novel risk assessment method - Zhang, Yifan; Liu, Jianfeng; Basang, Zhuoma; Yang, Qianxun; Chen, Hongce; Chen, Shuo; Li, Shaogang; Lei, Changgui; Fang, Mingyan; Liu, Huanhuan; Jin, Xin; Wang, Yingying (Frontiers in Genetics, 2025)
The hypoxia-ischemia (H-I) diseases share some common mechanisms which may help to delay the diseases’ processing. However, the shared features are still unclear due to the lack of large scale high-quality multi - omics data that specifically target the same disease, population, and tissues/cells. In this study, we developed a novel risk assessment method to analyze four H–I diseases including eclampsia/preeclampsia (PE), pulmonary arterial hypertension (PAH), high-altitude polycythemia (HAPC), and ischemic stroke (IS). A combined new evaluation score was designed to integrate evaluation information from genomics, transcriptomics, proteomics, and metabolomics in previous researches. Genes were then divided into different groups according to their risk assessment score. The most significant group (direct biomarkers) contained genes with direct evidence of association to H-I disease: PIEZO2 and HPGD (shared), TSIX and SAA1 (PAH - specific), GSTM1, DNTT, and IGKC (HAPC - specific), LEP, SERPINA3, and ARHGEF4 (PE - specific), CD3D, ITK, and RPL18A (IS - specific). The groups ‘Intermediate crucial biomarkers’ contained genes played important roles in H-I disease related biological processes: CXCL8 (shared), HBG2, GRIN2A, and FGFBP1 (PAH - specific), FAM111B (HAPC - specific), C12orf39 and SLAMF1 (PE - specific). The genes lacking disease-association evidence but with similar characteristics with the above two groups were considered as ‘potential minor-effect biomarkers’: are SRRM2 - AS1 (shared), ATP8A1 (PAH - specific), RXFP1 and HJURP (HAPC - specific), HIST1H1T (PE - specific). With the development of biological experiments, these intermediate crucial and potential minor-effect biomarkers may be proved to be direct biomarkers in the future. Therefore, these biomarkers may serve as an entry point for subsequent research and are of great significance.